Cardiovascular daytime varying effect in cardiac surgery on surgical site infections and 1-year mortality: A prospective cohort study with 22, 305 patients. (24th April 2019) - Sommerstein, Rami; Marschall, Jonas; Kuster, Stefan P.; Troillet, Nicolas; Carrel, Thierry; Eckstein, Friedrich S.; Widmer, Andreas F.; ,
Abstract: Afternoon aortic valve replacement surgery may provide perioperative myocardial protection and improve patient outcomes compared with morning surgery. The results of our large observational study based on Swiss cardiac surgical site infection surveillance data suggest that the current evidence is insufficient to generally promote afternoon cardiac surgeries.